IDENTIFYING BARRIERS TO GROWTH FOR PRO-DEVELOPMENT FINANCIAL PRODUCTS IN THE UK MARKET - Go Jefferies, Josephine (2009)
This dissertation is the outcome of qualitative research into pro-development financial products marketed to UK investors using grounded theory to analyse the performance of five products and determine barriers to growth for the sector. The study aims to understand what types of investors the products were designed to appeal to and what methods they are using to market them. Telephone interviews were conducted with UK senior managers in strategic marketing roles to learn about the performance and product design processes. Secondary sources were used to prepare the interview guide and triangulated with primary data using grounded theory. The author investigates behavioural drivers for potential investors using literature from social capital, public goods theory, social marketing, social development funds and CSR, economic embeddedness, moral economy, new product development processes, organisational field theory and an agent-theoretic view of institutional markets. A framework that investigates widening participation amongst a spectrum of investor types is used to test the product design and marketing approaches used by issuing institutions.